Study on Modern Indian Scholars: Views on Religious Tolerance: Exploring the Perspectives of Modern Indian Scholars on Religious Tolerance (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The powerful methodology of Islam towards life is a main issue of conversation in Iqbal'sphilosophical and different works. He tracks down extraordinary social worth in the foundation ofprophethood. The presence of prophets at various phases of chronicled advancement is with regards tothe persistent advancement in all fields of human civilization. It gives novel idea, better approach forenquiry and better approach for information and activity. Prophethood in Islam addresses the creatingsystem of human astuteness. In this unique situation, Iqbal gives the case of the prophet of Islam who,he says, remains between antiquated world and modem world. Subsequent to enlisting its vehementpresence in bygone eras, the possibility of strict universals turned out to be progressively famousamong the modem Indian scholars - both Hindu and Muslim. Among these, the first to give a strongvoice was Rabindranath Tagore. He provided guidance to Indian way of thinking. He was a man whochanged the prospect of individuals about strict doctrines and odd notions. He was a spiritualist,humanist, writer, thinker and the incredible devotee of Brahmosamaj. Affected by Brahmosamaj heattempted to eliminate the notions of Hindu religion. He pictured a variant of Hindu religion which was amix of certain components of Brahmosamaj and a few components of standard Hinduism.